2017
DOI: 10.3139/146.111549
|View full text |Cite
|
Sign up to set email alerts
|

Ion transport and phase transformation in thin film intercalation electrodes

Abstract: Thin film battery electrodes of the olivine structure LiFePO4 and the spinel phase LiMn2O4 are deposited through ion-beam sputtering. The intercalation kinetics is studied by cyclo-voltammetry using variation of the cycling rate over 4 to 5 orders of magnitude. The well-defined layer geometry allows a detailed quantitative analysis. It is shown that LiFePO4 clearly undergoes phase separation during intercalation, although the material is nano-confined and very high charging rates are applied. We present a modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This model was compared and fitted with multi-particle (bulk) experiments using LiMn 2 O 4 and LiCoO 2 cathodes in organic solvents and is used here, in the present work, to analyze the behavior of nanosystems. Planar and spherical geometries are approximations generally used to mimic lithium manganese oxide (LMO) thin films, porous electrodes and single particles [2,3], which are the most common types of electrode material configuration [4][5][6][7][8][9][10][11]. LMO nanorods, which can be compared with a cylindrical geometry, have also been used [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This model was compared and fitted with multi-particle (bulk) experiments using LiMn 2 O 4 and LiCoO 2 cathodes in organic solvents and is used here, in the present work, to analyze the behavior of nanosystems. Planar and spherical geometries are approximations generally used to mimic lithium manganese oxide (LMO) thin films, porous electrodes and single particles [2,3], which are the most common types of electrode material configuration [4][5][6][7][8][9][10][11]. LMO nanorods, which can be compared with a cylindrical geometry, have also been used [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Since those effects can't be taken into account for measurement of diffusion coefficients the experimental values span a large range from 10 × 10 −13 -10 × 10 −8 cm 2 /s at room temperature [119][120][121]. Where more detailed studies with knowledge of the microstructure showed PLD produced thin films to be on the lower end (10 × 10 −11 -10 × 10 −12 cm 2 /s decreasing with decreasing Li content) [122] as well as for electrodeposited and sintered thin films with 50 nm grain size (10 × 10 −11 -10 × 10 −9 cm 2 /s [123] and the Li diffusion coefficient significantly dropping for thick electrodes (10 × 10 −11 -10 × 10 −8 cm 2 /s for 304 -112 µm electrode thicknesses) [124].…”
Section: Limn 2 O 4 Other Manganese Oxides and Elementary Chemical I...mentioning
confidence: 99%